Donkey Slaughter in Brazil: A Regulated Production System or Extractive Model? - Sharacely de Souza Farias; Aline Rocha Silva; Rayane Caroline Medeiros do Nascimento; Marisol Parada Sarmiento; Tobyas Maia de Albuquerque Mariz; Pierre Barnabé Escodro (Animals)
Donkeys were traditionally used as draft animals for transporting cargo, as a means of transportation, and for riding purposes before the advent of mechanization. Following this historical shift, their economic significance declined, making them targets for other industries, such as Chinese industries that use donkey skin to extract gelatin (ejiao). Since donkey slaughter is not a regulated activity in Brazil, the welfare and survival of donkeys are increasingly at risk as demand for their skins rises. Complaints filed by public agencies in Brazil have raised concerns about the donkey slaughter chain in the country, questioning whether this production system operates under regulated standards or follows an extractive model. The objective of this study was to evaluate the production system of donkeys destined for slaughter in Brazil through physical and hematological assessments, aiming to identify potential systemic failures that may compromise animal welfare. To achieve this, physical and hematological evaluations were conducted on a group of 104 abandoned donkeys. The physical assessments aimed to determine the animals’ sex, estimate their age, and evaluate their body condition score (BCS). These were conducted through examination of the genital organs and dental arcades, with the neck evaluated using a scale from 0 to 4 and the body condition assessed using a scale from 1 to 9, respectively. Hematological assessments included the measurement of hematocrit (HT), total plasma protein (TPP), and plasma concentration of fibrinogen. Most of the donkeys were entire males (n = 50–48.08%), with a median age of 15.1 years. The body condition score was 2 or 3 (n = 36, 52%), and the neck condition score was 1 (n = 3, 37.5%). The majority of animals had hematocrit levels above 25%, total plasma protein levels below 7.5 g/dL, and fibrinogen levels exceeding 400 mg/dL. Based on the data analysis, the animals were characterized as being in poor health, since all groups exhibited altered body and neck condition score, plasma fibrinogen concentration, and total plasma protein. These parameters may be indicative of malnutrition and systemic inflammation, even though other laboratory results showed no signs of disease. Activities characterized by mistreatment contribute to an unsustainable extractive model.